Surgical treatment of paraphimosis in dogs: 4 cases - Nuriza Zamirbekova; Kurtulus Parlak; Iremsu Satici; Hilmican Ergin; Sena Yazici; Ebrar Merve Eris; Melek Yildiz; Fahrettin Alkan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to evaluate the use of surgical methods concerning the severity of persistent paraphimosis and describe the surgical techniques. Materials and Methods: The study material consisted of 4 dogs with paraphimosis. Based on anamnesis and clinical examination, 3 dogs were diagnosed with idiopathic permanent and one dog with traumatic paraphimosis. According to diagnoses and findings, patients underwent preputial advancement, partial penile amputation, phallopexy, and total penile amputation. Results: Recurrence of disease 1 week following surgery was recorded as postoperative complication in the first patient with preputial advancement. Intermittent bleeding in the surgical field in the second patient undergoing partial penile amputation continued for 3 days. No complications were observed as a result of the preputial advancement and phallopexy procedures performed for the treatment of the third case. The surgical wound healing time was recorded as one week in the second and third cases. In the fourth case, intermittent bleeding persisted for 12 days postoperatively and mild dermatitis was noted at the surgical site. According to the information received from the patient owners on the 30th day after the surgery, it was noted that there was no recurrence of the disease and no complications were encountered. Conclusion: According to the results of our study preputial advancement surgery technique alone was unsuccessful when the length of the prolapsed penis from the prepuce was 1,5 cm or more in patients with permanent paraphimosis. In addition, in cases where the disorder of the penile shaft and urethra allows, partial penile amputation should be preferred to total penile amputation.